Identifying and Hierarchizing the factor of Delay Factors with Interpretive Structure Modelling a case in Indian Thermal Power Plant - Kaushik A. J Naik; J N Ramprasad; Giridhar Kamath; H. C. Shiva Prasad (International Journal of Mechanical Engineering and Technology, 2018)
Project(s) to succeed four key factors are important; they are manpower, finance, material and time. The finance is an essential component than the rest and the key role played by the finance department is critical for project completion success. The project manager ensures that the project completes within timeline, as every delay incurs cost-overrun. The consulting firm is responsible for the project that probes the causes for time and money delay factors. This study sheds light on the delay factors that causes cost escalation on the project managers to have to deal with during the project. Cost escalation of the project is a significant cause of concern to the client as the requirement to make financial arrangement for the project is very important. The objective is to list and rank the significant causes of delay that occurs during the construction of the project based on prior work done by other researchers and experts in the field from the company. The ranking the delays is done by three methods-Relative Importance Index (RII), Importance Index (IMP.I) and Total Risk Score (TRS). Using the three approaches the delay causes are ranked based on the responses from experienced projects managers via survey questionnaire in projects site. The cost of escalation by di-graph shows nine delay causes were considered as critical causes and the nine variables were used in developing and Interpretive Structural Model (ISM) showing the interrelationship among the delay causes. If was found that the cost of the project increases with a delay in completion time, based on the ranking of the delay causes. Based on the results obtained recommendations are given to mitigating these delays.
Keywords: M11; O22; G30; 330; cost escalation; finance; interpretive structural modelling; project management